HUBUNGAN ANTARA POLA KONSUMSI PANGAN DAN AKTIVITAS FISIK DENGAN KEJADIAN OSTEOPOROSIS PADA LANSIA DI PANTI WERDHA BOGOR - Avliya Quratul Marjan; Sri Anna Marliyati (Jurnal Gizi dan Pangan, 2013)
The objective of this study was to analyze relationship between food consumption and physical activity with incidence of osteoporosis in elderly at nursing home in Bogor. The design of this study was cross sectional. Subjects were taken purposively with certain criteria and the number of subjects obtained were 37 elderly. Results showed that the adequacy level of energy and protein were normal, phosphor was in adequate category and calcium was in deficient category. There was no significant relationship between nutritional status, the adequacy level of energy, protein and phosphor with risk of osteoporosis (p>0.05). However, there was a significant relationship between the adequacy level of calcium and physical activity level with risk of osteoporosis (p<0.05). The deficit adequacy level of calcium and physical activity was a risk factor for the risk of osteoporosis.